"We Were in White Homes as Black Children:" Caribbean Youth's Stories of Out-of-home Care in Ontario, Canada. Issue 3 (2nd September 2021) - Akuoko-Barfi, Charlotte; McDermott, Tearney; Parada, Henry; Edwards, Travonne
ABSTRACT: This article reports on narrative interviews conducted as part of the Rights for Children and Youth Partnership Project exploring the experiences of 25 Black Caribbean youth (ages 16–26) who have navigated the child protection system in Ontario, Canada. An introduction to transracial fostering in Ontario is provided, and participants' reflections on the significance of caregivers' race in their experiences of out-of-home care are presented. Critical Race Theory and Anti-Black Racism are used as theoretical frameworks to guide the discussion. Themes discussed include adapting to White environments and community visibility; appropriate haircare, skincare, and food in placements; navigating Whiteness and anti-Black racism; and sense of connection with caregivers.